Characterization of crude bacterial urease for CaCO₃ precipitation and cementation of silty sand - He, Jia (2022)
Biocementation catalyzed by ureolytic bacteria or enzyme urease is a promising technique for the treatment of liquefiable soil. Silty sand is often encountered in natural conditions and is often prone to earthquake liquefaction. However, the applicability of the biocementation to silty sand is still a challenge. In this study, we proposed and tested a new method of applying the biocementation to silty sand. In this method, crude urease obtained from the lysis of ureolytic bacteria was used for the soil treatment instead of using live bacteria directly. It was found that crude urease could be successfully obtained from bacteria using the ultrasonic cell lysis method. The activity of the crude urease was relatively high in 0.01-1 mol/L of urea concentrations and 5-11 pH values and increased in temperature in the tested range (10°C-50°C). The results of the CaCO3 precipitation reaction tests showed that crude urease was capable of hydrolyzing urea and could be used in the biocementation treatment when the initial urea concentration was not higher than 0.5 mol/L. Triaxial consolidated undrained tests and CaCO3 content measurements were conducted on the silty sand samples treated by either urease or live bacteria. Silty sand samples treated by urease had higher shear strengths and more dilative stress-strain responses during the undrained shear as compared with the samples treated by live bacteria. In the bacteria-treated samples, CaCO3 was prone to accumulating at the injection side of the samples, while the treatment using crude urease can alleviate such a problem by showing higher CaCO3 contents at farther locations of the samples.